BROEKSMA, Albertonie Herman Inventory of documents - BROEKSMA, Albertonie Herman (ARCA, 2018)
Private papers of A.H. Broeksma, 1932 Law advisor to General Hertzog; Attorney-General Cape Province[1939-1946]
COVERAGE 1960-1961, 1967; 2 Files; 0.11 metre
Keywords: BROEKSMA, Albertonie Herman; Advocate